Ecological implications for sustainable stormwater systems in the tallgrass prairie region - Culbertson, Trisha L. (Kansas State University, 2008)
Urban stormwater is one of the leading causes of water quality impairment and stream channel degradation in the United States. In an effort to address the negative effects of stormwater runoff on receiving aquatic systems, Best Management Practices for stormwater, including ecologically-designed stormwater systems, are becoming more common across the urban landscape. Throughout eastern Kansas and the rest of the Midwestern United States, prairie grasses are beginning to receive attention for their potential to enhance infiltration within these systems. However, the function of vegetated stormwater systems and the influence of factors such as vegetation age on infiltration and system performance are not well understood because monitoring data for these systems is limited. When performance data is collected, it often pertains only to the hydraulic and water quality aspects of the system but neglects any assessment of the integrity of the ecosystem functions on which the system's performance is dependent. The objective of this study was to address the need for an assessment tool that considers the ecological integrity, or health, of ecologically-designed stormwater systems, as well as to fill the gap in the literature regarding the function of ecologically-designed stormwater systems in the tallgrass prairie region. Since many of the eco-based stormwater practices in the region rely upon the establishment of native prairie grasses to enhance infiltration on the site, the specific focus of this study was to gain a better understanding of infiltration processes in ecologically-designed systems and the extent of our ability to regain these processes through prairie restoration in previously disturbed urban sites. To address these objectives, two stormwater systems at different stages of vegetative maturity were examined. In general, ecosystem health scores were higher for the more mature system and could be used to guide future management decisions at both sites. Results from the hydraulic analysis indicate the function of the system may improve over the course of the growing season, but statistical relationships between system age and infiltration rate could not be established.
Keywords: storm water; BMPs; ecological assessment; infiltration; tallgrass prairie; Engineering, Agricultural (0539); Engineering, Environmental (0775)